A Qualitative Study on Breastfeeding among Mothers with Intellectual Disabilities: Perspectives of Nurse-Midwives and Public Health Nurses - Kinuko Sugiura; Kazuko Fujisawa (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2022)
Background: Breastfeeding is important for maintaining and promoting lifelong health and bonding between mother and child. Professional support in the early postpartum period is key to successful breastfeeding. Mothers usually learn parenting skills in the early postpartum period, but mothers with intellectual disabilities (IDs) require special consideration due to their low learning ability. The views of midwives and public health nurses regarding breastfeeding support for mothers with intellectual disabilities in the early postpartum period need to be clarified. Purpose: The study aimed to describe the perspectives of nurse-midwives (NMWs) and public health nurses (PHNs) on breastfeeding for mothers with intellectual disabilities. Methods: Data obtained from semi-structured interviews with five NMWs and five PHNs with experience in caring for postpartum mothers with IDs were analysed using a conventional content analysis approach. Results: The analysis yielded two categories ‘Determining whether breastfeeding is the best’ for NMWs and ‘Desire for strengthened support for establishing breastfeeding during postpartum hospitalization’ for PHNs. The former comprised three subcategories: ‘Effects of complications and abnormal deliveries’, ‘Evaluation of adaptability’, and ‘Evaluation of support person's capability’, while the latter consisted of ‘Focus on the advantages of breastfeeding’, ‘Focus on the disadvantages of artificial breastfeeding’, and ‘Desire for NMWs’ support during postpartum hospitalization to establish breastfeeding’. It was established that NMWs had short-term perspectives that considered the physical trauma and fatigue sustained by mothers during childbirth and they tried to minimize their physical and emotional burden, whereas PHNs had long-term perspectives that considered the impact of breastfeeding on children’s future. Conclusion: Successful breastfeeding by mothers with IDs requires a change in NMWs’ awareness and the development of a system and instructional media that enable NMWs to perform their responsibilities in accordance with the basic principles of breastfeeding. Additionally, policies are required to promote this practice.